Polymeric drugs based on conjugates of synthetic and natural macromolecules. II. Anti-cancer activity of antibody or (Fab')(2)-targeted conjugates and combined therapy with immunomodulators - Ríhová, B; Jelínková, M; Strohalm, J; Subr, V; Plocová, D; Hovorka, O; Novák, M; Plundrová, D; Germano, Y; Ulbrich, K (Journal of controlled release, 2000)
We provide data on in vivo targeting of the Thy 1.2 (CDw90) cell surface receptor expressed on neoplastic T cells, mouse EL4 T cell lymphoma. The targeting antibody and the anticancer drug, doxorubicin (DOX) were conjugated to a water-soluble copolymer based on N-(2-hydroxypropyl)methacrylamide (HPMA) acting as a carrier responsible for controlled intracellular release of the conjugated drug. The in vivo therapeutic efficacy of HPMA copolymer-bound DOX targeted with anti-EL4 antibody, polyclonal anti-thymocyte globulin (ATG), monoclonal anti-Thy 1.2 antibody or its F(ab')(2) fragment was compared with the efficacy of DOX conjugated to HPMA copolymer containing nonspecific IgG or bovine serum albumin (BSA). Anti-EL4 antibody-targeted conjugate caused a significant retardation of tumor growth and an extension of the life span of treated mice. The effect was comparable with that of HPMA copolymer-bound DOX targeted with ATG, anti-Thy 1.2 antibody or its F(ab')(2) fragment. However, considerable antitumor effect was seen also in conjugates targeted instead of specific antibodies with syngeneic nonspecific IgG or BSA. Patients with advanced cancer are often immunocompromised due to dysfunction of their immune system induced by cancer and cytotoxic drugs. A significant decrease of unwanted side-effects of targeted drugs against a number of vital organs was already documented. In this study we have compared immunotoxic effects of free DOX with those of its antibody-targeted form on NK cells and cytolytic T lymphocytes (CTLs) isolated from C57BL/10 mice bearing EL4 T cell lymphoma. In the same model we have tested the combination therapy with immunomodulators (beta-glucan or AM-2) injected together with targeted daunomycin. We have observed a significant protective effect of targeted DOX against NK cells and CTLs. Moreover, the data revealed that combination therapy considerably enhances antitumor efficacy of the targeted anticancer drug.
Keywords: lymfom; imunoglobuliny - Fab fragmenty; náhodné rozdělení; methakryláty; sérový albumin; techniky in vitro; Tumor Cells, Cultured; Adjuvants, Immunologic; Delayed-Action Preparations; imunoglobulin G; T-Lymphocytes; Drug Carriers; Immunoglobulin Fab Fragments; adjuvancia imunologická; doxorubicin; Drug Synergism; Antineoplastic Agents; rozpustnost; Doxorubicin; Lymphoma; Serum Albumin; zvířata; myši; myši inbrední C57BL; buňky NK; synergismus léků; časové faktory; nádorové buňky kultivované; polymery; Killer Cells, Natural; Mice; Polymers; Cattle; Male; protilátky; Mice, Inbred C57BL; skot; Solubility; nosiče léků; léky s prodlouženým účinkem; Antibodies; In Vitro Techniques; protinádorové látky; T-lymfocyty; Animals; mužské pohlaví; Immunoglobulin G; Methacrylates; kombinovaná farmakoterapie; Random Allocation; Time Factors; Drug Therapy, Combination